Initial pH influences in-batch hydrogen production from scotta permeate. (25th May 2017) - Vasmara, Ciro; Marchetti, Rosa
Abstract: We studied the influence of initial pH on hydrogen (H2 ) production using permeate from scotta (a partially deproteinized cheese whey from ricotta production) as substrate (51 g L −1 lactose). Dark fermentation was carried out at 35 °C in laboratory batch reactors, in an unbuffered system. Hydrogen production and metabolite (volatile fatty acids, ethanol, and lactic acid) evolution during a 96-h period were monitored in reactors with initial pH varying in the range 4–10. In all reactors, H2 production started only when pH fell below 6. However, it was much higher (+31%) in the reactors with initial alkaline pH. We conclude that H2 production occurs only at acidic pH values, but initial alkaline pH values increase the overall H2 production in dark fermentation of lactose-rich substrates. Graphical abstract: Highlights: We studied the pH effect on H2 production in dark fermentation of scotta permeate. At the start of fermentation pH decreased or increased, regardless of its initial value. Hydrogen production always started when the pH of the fermentation broth was below 6. However, H2 production rate and yield were much higher when initial pH was alkaline.